Three-stage method of forecasting energy consumption levels in the economy with regard for regional energy saving potentials - Maistrenko N.Yu.; Maliarenko O.Ye.; Horskyi V.V. (General Energy Institute of the National Academy of Sciences of Ukraine, 2020)
We perfected the known two-stage method of forecasting energy consumption levels by applying its methodical approaches for three hierarchical levels of the structure of Ukrainian economy: country, regions, types of economic activity in regions. This approach makes it possible to determine the demand for fuel and energy resources at the regional levels of structuring the economy with regard for the specific features of their economic development. According to regional energy efficiency programs, it is possible to estimate more accurately the energy saving potentials and volumes of the replacement of scarce fuels with their cheap local types.The three-stage method is based on the refined normative method that is used at three hierarchical levels with regard for the estimated energy saving potentials from structural and technological shifts in the economy. The forecasts obtained agree with each other by Kulyk's method twice. The country-level forecast is consistent with the forecast for total regional energy consumption. For each region, the forecast of regional energy consumption is consistent with the forecast of total energy consumption at the levels of types of economic activity in the region with regard for structural and technological shifts. If the coordination of consumption levels between the types of economic activity and the region will introduce corrections to the regional energy consumption, then the coordination of levels of the country and regions is carried out at the second time. In other words, forecasting is carried out at three levels with two matches of the results of forecasting energy consumption –- between the first and second as well as second and third levels. If it is necessary to correct the forecasts of second level, reconciliation between the forecasts of first and second levels is performed again. Kulyk's vector method is used to agree on predictive decisions. We also present a method for calculating the forecasts of energy consumption at three hierarchical levels with the corresponding agreement of these forecasts.Based on the described methodology and estimated volumes of energy saving potentials at regional levels and for more significant types of economic activity in the regions, we performed a forecast of heat energy consumption for the period to 2040 , taking into account the volumes of technological energy saving in the regions.